Effective Dose of Moringa Leaf Extract (Moringa oleifera Lamk.) to Descrease Total Cholesterol Levels in Streptozotocin-Induced Male Wistar Rats - Pipiet Wulandari; Athiyah Fi Ramadani; Suryono Suryono; Ali Santosa (Journal of Agromedicine and Medical Sciences, 2022)
Lipid metabolic disorder in hyperlipidemia characterized by an increase in the entire lipid profile in the blood. In 2019, the global prevalence of hyperlipidemia was 64.2%. Many patients with diabetes mellitus developed to hyperlipidemia. Diabetes mellitus characterized by hyperglycemia that caused by insulin production defects or decreased insulin resistance. Hyperglycemia in this study resulted from the injection of a streptozotocin dose of 45mg/kgBB intraperitoneally. Hyperglycemia could induced hyperlipidemia. It is due to increased lipid synthesis resulting in overproduction of HMG-CoA and ROS. Moringa leaves contain active substances such as flavonoids and vitamin C that act as antioxidants. This study was conducted to find out the effective dose of moringa leaf extract to lower the total cholesterol levels of male Wistar rats induced by streptozotocin. The dose of moringa leaf extract was divided into 5 groups, namely 62.5 mg/kgBW, 125 mg/kgBW, 250 mg/kgBW, 500 mg/kgBW, and 1000 mg/kgBW. The analysis of the data in this study was a Pearson correlation test that showed p< 0.05. It demonstrated that administration of moringa leaf extract correlated with decreased cholesterol levels of male Wistar rats. The effective dose of moringa leaf extract was calculated using a linear regression test. The equation obtained from the regression test was y= 0.0739x + 153.59, so the dose of moringa leaf extract that effectively lowers the total cholesterol levels of male Wistar rats was 528.96 mg/kgBW. Keywords: hyperlipidemia, diabetes mellitus, cholesterol, Moringa oleifera Lamk., streptozotocin